Awake insertion of a Laryngeal Mask Airway-Proseal™ as alternative to awake fiberoptic intubation in management of anticipated difficult airway in ambulatory surgery - Zaballos,Matilde (2016)
Abstract Background and objectives The decision whether to manage an ambulatory patient with a previously documented difficult airway with a supraglottic device remain controversial. We report an awake insertion of a Laryngeal Mask Airway Proseal™ in a patient with known difficult airway scheduled for ambulatory surgery. Case report A 46-yr-old woman was programmed as a day case surgery for breast nodule resection. Her anesthetic record included an impossible intubation with cancelation of surgery and subsequent awake fibroscopic intubation. She reported emotional distress with the previous experience and declined this approach. In view of the previous experience, an awake airway control with a Laryngeal Mask Airway Proseal™ was planned after explaining and reassuring the patient. After adequate topicalisation, a size 4 Laryngeal Mask Airway Proseal™ was successfully inserted after two attempts, and their patency was confirmed by capnography. Anesthesia was induced intravenously and the surgery was uneventful. Conclusion We describe a feasible alternative strategy to awake intubation in a patient with known difficult airway undergoing ambulatory surgery. In this specific clinical situation, if tracheal intubation is deemed unnecessary, awake supraglottic airway might allow adequate ventilation and their use should be considered.